(untitled) (PUBMET, 2023)
“You don’t communicate with anyone purely on the rational facts or ethics of an issue. … It is only when the other party is concerned or feels threatened that he will listen—in the arena of action, a threat or a crisis becomes almost a precondition to communication.” – Saul Alinsky, Rules for Radicals Two decades ago, discussions about ethics were relatively rare in publishing. Retractions were almost unheard of. Science was ‘self correcting’. Today, the rise of paper mills, peer review manipulation, and predatory journals, alongside an increased awareness of a lack of reproducibility, have forced publication ethics up the agenda. What has caused this surge in issues and what can be done to take advantage of the concern about these ‘crises’ to tackle these problems at scale, to ensure the future integrity of both research and its publication?